2011
DOI: 10.1094/phyto-03-11-0091
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Yield Response of Hybrid Field Corn to Foliar Fungicides in the U.S. Corn Belt

Abstract: The use of foliar fungicides on field corn has increased greatly over the past 5 years in the United States in an attempt to increase yields, despite limited evidence that use of the fungicides is consistently profitable. To assess the value of using fungicides in grain corn production, random-effects meta-analyses were performed on results from foliar fungicide experiments conducted during 2002 to 2009 in 14 states across the United States to determine the mean yield response to the fungicides azoxystrobin, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 46 publications
5
51
1
11
Order By: Relevance
“…We have not found other studies of seed treatments clearly addressing this point, but a similar inverse correlation (low baseline yield : high yield response to treatment) as here found for Calthio C has been reported also for fungicides applied as foliar sprays in maize (Paul et al, 2011). The same study found, that fields having a low baseline yield also had a relatively high disease index and thereby -theoretically -a larger potential to respond to antifungal treatments.…”
Section: Factors Influencing the Effect Of Seed Treatmentsupporting
confidence: 81%
“…We have not found other studies of seed treatments clearly addressing this point, but a similar inverse correlation (low baseline yield : high yield response to treatment) as here found for Calthio C has been reported also for fungicides applied as foliar sprays in maize (Paul et al, 2011). The same study found, that fields having a low baseline yield also had a relatively high disease index and thereby -theoretically -a larger potential to respond to antifungal treatments.…”
Section: Factors Influencing the Effect Of Seed Treatmentsupporting
confidence: 81%
“…Portanto, o uso de piraclostrobina em condições de baixa severidade de doenças não é indicado para os dois híbridos em questão, visto que não houve diferença de produtividade entre os tratamentos que receberam aplicação de piraclostrobina e a testemunha. PAUL et al (2011) relataram elevada ocorrência de resultados negativos de rendimento, ou seja, menores produtividades em área tratadas com fungicida em relação às áreas não tratadas, no entanto, tal resultado não foi evidenciado no presente trabalho. KOZLOWSKI et al (2009) relataram um efeito positivo da aplicação de piraclostrobina sobre o rendimento de grãos de feijoeiro.…”
Section: Resultsunclassified
“…Segundo os autores, em 472 tratamentos em que se compararam áreas tratadas e não tratadas com fungicidas, 80% apresentaram resposta de produtividade positiva a uma aplicação de fungicida e, em 20% dos casos, foi obtida resposta de produtividade nula ou negativa à aplicação. Em outro estudo, a resposta de redução de produtividade em relação à testemunha foi obtida em 26 a 48% dos casos, dependendo do fungicida utilizado (Paul et al, 2011). Resultados semelhantes foram obtidos em outros estudos (Khan & Carlson, 2009;Nason, et al, 2007;Nelson et al, 2010;Swoboda & Pedersen, 2009).…”
Section: Discussionunclassified
“…No entanto, em diversas situações, esses aumentos não resultaram em benefício econômico, ou seja, o aumento de produtividade foi menor que o custo requerido para a realização da aplicação do fungicida. Resultados semelhantes têm sido observados em outros trabalhos (Paul et al, 2011;Wise & Mueller, 2011). A obtenção de benefício econômico positivo da aplicação de fungicida não depende apenas do aumento de produtividade obtido, mas, também, do custo necessário para a aplicação do fungicida e do preço de mercado da saca de milho.…”
Section: Discussionunclassified
See 1 more Smart Citation